2020
DOI: 10.3390/ijms21020617
|View full text |Cite
|
Sign up to set email alerts
|

Scars or Regeneration?—Dermal Fibroblasts as Drivers of Diverse Skin Wound Responses

Abstract: Scarring and regeneration are two physiologically opposite endpoints to skin injuries, with mammals, including humans, typically healing wounds with fibrotic scars. We aim to provide an updated review on fibroblast heterogeneity as determinants of the scarring–regeneration continuum. We discuss fibroblast-centric mechanisms that dictate scarring–regeneration continua with a focus on intercellular and cell–matrix adhesion. Improved understanding of fibroblast lineage-specific mechanisms and how they determine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 113 publications
(139 reference statements)
2
62
0
Order By: Relevance
“…TGF-β signaling is the most important pathway that determines granulation tissue formation and wound healing outcome (Desmouliere et al, 1993;Margadant and Sonnenberg, 2010;Lichtman et al, 2016;Jiang and Rinkevich, 2020). Deficiency in TGF-β1 expression as in CD18 −/− (Peters et al, 2005) or dysregulated TGF-β1 signaling as in diabetic foot ulcers (Badr et al, 2012;Zhang et al, 2016) and chronic venous leg ulcers (Sindrilaru et al, 2011) result in chronic non-healing wounds, whereas excessive TGF-β1 leads to contracture and scarring as seen in hypertrophic scars and keloid scars (Jagadeesan and Bayat, 2007;Chalmers, 2011;Wynn and Ramalingam, 2012).…”
Section: Mscs Act As Rheostat Of Trophic Factors To Re-establish Tissmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β signaling is the most important pathway that determines granulation tissue formation and wound healing outcome (Desmouliere et al, 1993;Margadant and Sonnenberg, 2010;Lichtman et al, 2016;Jiang and Rinkevich, 2020). Deficiency in TGF-β1 expression as in CD18 −/− (Peters et al, 2005) or dysregulated TGF-β1 signaling as in diabetic foot ulcers (Badr et al, 2012;Zhang et al, 2016) and chronic venous leg ulcers (Sindrilaru et al, 2011) result in chronic non-healing wounds, whereas excessive TGF-β1 leads to contracture and scarring as seen in hypertrophic scars and keloid scars (Jagadeesan and Bayat, 2007;Chalmers, 2011;Wynn and Ramalingam, 2012).…”
Section: Mscs Act As Rheostat Of Trophic Factors To Re-establish Tissmentioning
confidence: 99%
“…Granulation tissue formation is the hallmark of the proliferation phase. During granulation tissue formation, the polarization of reparative M2 macrophages, proliferation and differentiation of contractile myofibroblast, wound contraction, new vessel formation, and matrix deposition are concomitantly initiated ( Gabbiani et al, 1971 ; Flanagan, 1998 ; Gabbiani, 1998 ; Hinz and Gabbiani, 2003 ; Hinz, 2007 , 2016 ; Hinz et al, 2012 ; Jiang and Rinkevich, 2020 ). Recent studies revealed that myofibroblasts in granulation tissue derived from Engrailed-1 (En1)-positive lineage by lineage tracing studies ( Rinkevich et al, 2015 ; Jiang et al, 2018 ) or from a subset that expresses delta like non-canonical Notch ligand 1 (Dlk-1) as the surface marker ( Driskell et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the identified populations, only fibroblasts expressing dipeptidylpeptidase IV are able to produce ECM, which is fundamental for wound healing [ 130 ]. Accordingly, the extent of scar formation depends on the transcriptomic profile of fibroblasts present in the wounds [ 131 ].…”
Section: Proliferation Phase Of Wound Healingmentioning
confidence: 99%
“…Among the various kinds of cellular NA, messenger RNA (mRNA; responsible for coding amino acid synthesis and thus protein translation) and micro RNA (miRNA; small non-coding RNA responsible for post-transcriptional gene regulation) are highly correlated to the cellular state and functionality [85]. In several examples involving pathological skin conditions, aberrant WNT5A and MMP1 mRNAs have a detrimental effect in squamous cell carcinoma, while upregulation of mRNAs in the TGFβ pathway (e.g., CTGF mRNA and FAP-α mRNA) are indicative of abnormal wound scarring [86,87]. Krt-16, TNF-α, IFN-γ, IL-23A, IL-12B, CD2, and VEGF mRNA are found to be overexpressed in psoriatic skin lesions [88].…”
Section: Nucleic Acidsmentioning
confidence: 99%